Highly Religious Young Poles in the Process of Transformation - Rafał Boguszewski; Janusz Mariański (The Francis de Sales Scientific Society (TNFS.PL), 2023)
The article describes highly religious young Poles who are at the stage of entering adulthood (aged 18-19 and attending the final grades of high school). In the empirical analysis, we use the existing data from quantitative research carried out in 1996, 2010, and 2021. The same methodology for the implementation of the survey, including sample selection, as well as a broadly comparable research tool, allowing to capture significant changes, tendencies, and trends that have occurred among young Poles in the last 25 years in terms of religiousness. The data show that despite a significant decrease in the percentage of people who define themselves as religious, and even more so as regularly practicing religion, the percentage of deeply religious people and regular religious practitioners remains relatively constant (about 5% of the population of young Poles who have reached the age of majority). The question arises whether the socio-demographic structure of this group remains stable over the time and whether and to what extent it differs from the structure of other groups, including less religious and non-religious people. The article attempts to answer this question.